Spätantiker Staat und religiöser Konflikt Imperiale und lokale Verwaltung und die Gewalt gegen Heiligtümer - Hahn, Johannes (Millennium-Studien / Millennium Studies, 2011)
The process of Christianisation brought with it a new form of violent conflict to the Roman world: religiously motivated attacks on places, objects or people. The most radical form of such conflicts were attacks on the sanctuaries of religious opponents- on temples, synagogues and Church buildings. The results were dramatic and the attacks demanded a reaction from all institutions, from the Emperor to the urban elites. This volume analyses the role of the law, the imperial and local administrations, and the relationship between the institutions and the new regional and local communities whichestablished themselves at the time.